2004
DOI: 10.5038/1827-806x.33.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Cave temperatures and global climatic change

Abstract: The physical processes that establish the cave temperature are briefly discussed, showing that cave temperature is generally strictly connected with the external climate. The Global Climatic changes can then influence also the underground climate. It is shown that the mountain thermal inertia causes a delay between the two climates and then a thermal unbalance between the cave and the atmosphere. As a consequence there is a net energy flux from the atmosphere to the mountain, larger than the geothermal one, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 0 publications
0
77
0
3
Order By: Relevance
“…The most important difference refers to the thermal inertia of caves, which explains time lags of up to several decades in the warming of the system (Badino 2004). This increased flux of energy from the atmosphere to the subterranean environment is expected to be deposited primarily in the superficial sections of caves (Badino 2004) and in other superficial subterranean habitats . Energy fluxes accumulating underground may have dramatic cascade effects on both physical and biological components of hypogean ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The most important difference refers to the thermal inertia of caves, which explains time lags of up to several decades in the warming of the system (Badino 2004). This increased flux of energy from the atmosphere to the subterranean environment is expected to be deposited primarily in the superficial sections of caves (Badino 2004) and in other superficial subterranean habitats . Energy fluxes accumulating underground may have dramatic cascade effects on both physical and biological components of hypogean ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the fungus is estimated to have killed >5.5 million bats in North America (National Park Service, 2013). Optimal growth of fungus isolates occurs at 5-10°C, with a maximum of 20°C (Blehert et al, 2009), similar to the microclimatic conditions found in caves; however, as landscape and climate contexts influence microclimatic conditions inside caves (Badino, 2004;Perry, 2013), a recent report found that WNS mortality in North America correlate with climate and landscape variables (Flory et al, 2012).…”
Section: Introductionmentioning
confidence: 69%
“…Frogs were more abundant in relatively warm cave sectors. The temperature of cave sectors is the result of complex interactions between external temperature, mean annual temperature, and air circulation of karstic systems (Badino 2004, Badino 2010. In winter, temperature is highest far from the surface, thus these sectors represent ideal shelters during hibernation.…”
Section: Discussionmentioning
confidence: 99%